Thyroid nodule size as an indicator for surgery - Hatem, Mohamed Abdulhameed; Farheen, Sumayya (International Surgery Journal, 2018)
Background: Several authors have questioned the accuracy of fine- needle aspiration cytology (FNAC) in large thyroid nodules. It’s the current practice to provide thyroidectomy to patient with thyroid nodules 4 cm or larger regardless of the FNAC results. The aim of the study is to answer two questions: is the size of nodule associated with higher risk of malignancy and is the size indication for surgery. Methods: Authors conducted a retrospective review of 201 patients who underwent thyroidectomy between 2011 and 2017 at Bahrain defense force hospital. Authors compared all thyroid nodules with benign FNAC and their final histopathology reports. Patients were divided into two groups based on the size of the nodule (< 4cm or >4cm) and indication of surgery. Results: 201 patients with thyroid nodule underwent thyroid surgery. 136 patients had nodule <4cm and 65 patients were ≥4 cm. For patients with nodules <4 cm, 37 patients (18.4%) had a malignancy, and for those with nodules ≥4 cm, 13 patients (6.4%) had a malignancy. comparison between size of the nodule, FNAC result and final histopathology: FNAC diagnosed 55 cases (27.3%) are malignant, final histopathology reported only 50 cases are malignant. But for benign cases FNAC and histopathology reports are showing same results, (p<0.05). Conclusions: Thyroid nodules ≥4 cm are not risk factor of malignancy. Thyroid nodules ≥4 cm with benign FNAC should not undergo thyroidectomy as false negative rate is low. Therefore, the decision for surgery ought not to be taken based on the size of the nodule.